Pengaruh Independensi, Komitmen Organisasi, Gaya Kepemimpinan dan Pemahaman Good Governance terhadap Kinerja Auditor Pemerintah - M. Adam Syafrizal Faiz; Sari Andayani (Universitas Batanghari Jambi, 2022)
This study purpose is to research and test “the effect of independence, organizational commitment, leadership style, and understanding of good governance on the performance of government auditors”. This research is quantitative using primary data. Population used in this study are auditors that work in the representative office of BPKP in East Java. This study is using non-probability sampling as sampling technique with the purposive sampling method. This research used 60 respondents as sample with the criteria of a.) government auditors b.) having work experience in the audit field for 5 years. This research is using PLS (Partial Least Square) as analysis technique. This study found that there is an effect of independence on the performance of government auditors, the effect of organizational commitment on the performance of government auditors, the influence of leadership style on the performance of government auditors, and the influence of good governance on the performance of government auditors.